2010
DOI: 10.1016/j.bcp.2009.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human placental P-glycoprotein expression and activity by MDR1 gene polymorphisms

Abstract: The ABC transporter P-glycoprotein is a product of the MDR1 gene and its function in human placenta is to extrude xenobiotics from the tissue thus decreasing fetal exposure. The goal of this investigation was to examine the effect of three polymorphisms in the MDR1 gene on the expression and activity of placental P-gp. In 199 term placentas examined, the C1236T variant was associated with 11% lower P-gp protein expression than wild type, while the C3435T and G2677T/A variants each were associated with a 16% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 26 publications
1
49
0
1
Order By: Relevance
“…As drug-drug interactions on ABC transporters may substantially affect the fate of drugs in organism, our findings should be taken into account when TDF is co-administered with compounds whose membrane transport is mediated by ABCB1 and/ or ABCG2 such as antiretrovirals [41] or other drugs administered in pregnancy [8]. Differences in ABCB1 expression between HIV-infected and noninfected women [42] as well as genetic polymorphisms leading to altered expression and function of the protein in the placenta [43] should also be considered when substrate drugs are prescribed.…”
Section: Discussionmentioning
confidence: 95%
“…As drug-drug interactions on ABC transporters may substantially affect the fate of drugs in organism, our findings should be taken into account when TDF is co-administered with compounds whose membrane transport is mediated by ABCB1 and/ or ABCG2 such as antiretrovirals [41] or other drugs administered in pregnancy [8]. Differences in ABCB1 expression between HIV-infected and noninfected women [42] as well as genetic polymorphisms leading to altered expression and function of the protein in the placenta [43] should also be considered when substrate drugs are prescribed.…”
Section: Discussionmentioning
confidence: 95%
“…Rahi et al (2008) reported that although SNPs altered the expression levels of P-gp in the human placenta, they did not have an effect on P-gp-mediated placental transfer of saquinavir. On the contrary, recent studies have shown that some homozygous mdr1 variants (C1236T, C3245T) are associated with an increase in placental P-gp efflux of paclitaxel (Hemauer et al, 2010). Transfected cell lines expressing the polymorphic variant (Q141K) of ABCG2 exhibit altered placental pharmacokinetics of glyburide (Pollex et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Ironically, in homozygous variants 1236T/T and 3435T/T the P-gp activity was apparently increased as shown by the transport of the prototypical P-gp substrate paclitaxel in the human term placenta compared to the homozygous wild type (C/C). The G2677T/A alleles also showed a trend toward increased P-gp activity than the homozygous wild type (C/C) (57). Further, a study by Rahi et al involving immunoblotting and genotyping by PCR in human placental samples indicated that the variant allele 3435T of P-gp caused significantly higher placental P-gp expression levels.…”
Section: Abc Transporters In the Placentamentioning
confidence: 99%